Titanium alloy anode plate and preparation method thereof

By preparing titanium alloy anode plates with high Mn content and gradient structure, the problem of existing anode materials being passivated and corrosion under high acid and high current conditions is solved, and efficient production and performance improvement of anode materials are achieved, which helps the development of the new energy industry.

CN119800272AActive Publication Date: 2025-04-11HUNAN HENGSHENG THERMAL MECHANICAL EQUIP CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510294179.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

Existing anode materials are prone to passivation and corrosion under high acid current conditions, resulting in narrow performance regulation of electrolytic manganese dioxide and difficult to meet the development needs of the new energy industry.

Method used

Using the titanium alloy anode plate and its preparation method, the titanium alloy anode plate is obtained by mixing Ti powder and Mn powder and then undergoing plasma spheroidization treatment. Then, the titanium alloy anode plate with high Mn content and gradient structure is prepared by flame spraying and gradient manganese permeation, and the surface is uniformly sprayed with copper nanowires to deposit graphene.

Benefits of technology

At 100A/m2 current density, the tank voltage is stable within 2.3-2.4 volts, the product adheres well to the anode, and there is no cracking and disengagement phenomenon, which significantly improves the anti-passivation performance and electrolytic efficiency of the anode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800272A_ABST
    Figure CN119800272A_ABST
Patent Text Reader

Abstract

The invention provides a titanium alloy anode plate and a preparation method thereof, and belongs to the technical field of anode plates. Ti powder and Mn powder are mixed, ball-milled and subjected to plasma spheroidizing treatment to obtain spherical TiMn alloy powder, the spherical TiMn alloy powder is sprayed to the surface of a titanium plate through flames, after gradient manganizing and surface treatment are conducted, copper nanowire deposition graphene and spherical TiMn alloy powder are evenly sprayed, drying is conducted, and the titanium alloy anode plate is obtained. The prepared titanium alloy anode plate can be used for electrolytic manganese dioxide production and has passivation resistance, the cell voltage can be stabilized within 2.3-2.4 V under the current density of 100 A / m < 2 > and the normal industrial electrolysis condition, the product and the anode are well attached, the cracking and separation phenomena are avoided, the defects of an existing industrial anode are overcome, and the titanium alloy anode plate can be applied to electrolytic manganese dioxide production. The anode is an ideal electrolytic manganese dioxide anode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anode plates, and in particular to a titanium alloy anode plate and a preparation method thereof. Background Art

[0002] Compared with chemical MnO2 and natural manganese dioxide, electrolytic MnO2 has the characteristics of high purity, strong adsorption, moisture absorption and oxidation, high activity, excellent discharge performance, etc. It is a key component of positive electrode materials for modern alkaline batteries, lithium batteries and sodium batteries. Generally, the activity of MnO2 increases with the increase of crystal water it contains. Crystal water can promote the diffusion of protons in the solid phase. γ-MnO2 is the most active among various crystalline MnO2.

[0003] At present, the main method for producing electrolytic MnO2 is high-temperature electrolysis, which means electrolyzing the electrolyte of MnSO4-H2SO4 system at high temperature (96-98℃) and certain current density to make Mn 2+ Redox reaction occurs on the anode to precipitate and deposit MnO2. When MnO2 is deposited to a certain thickness, the anode can be removed from the tank and MnO2 can be mechanically stripped off. 2+ Overcoming the reverse potential to diffuse to the anode is conducive to the precipitation of MnO2 to obtain γ-MnO2. The industry expects to develop in the direction of high acid and high current. However, the current anode materials have serious passivation and corrosion under high acid and high current conditions, which restricts the development of the electrolytic manganese dioxide (EMD) industry. In addition, the mechanical stripping of MnO2 causes great loss to the anode, requiring the anode to have high strength and ductility.

[0004] At present, the mainstream solution of the EMD industry to solve the problem of easy passivation corrosion of anode materials in high current density and high acidity electrolytic environment is to use Ti-based TiMn coated anodes. The reason why pure Ti is easy to passivate is that its oxide has extremely poor conductivity, while Mn oxide has good conductivity. Therefore, increasing the Mn content in the TiMn coating makes it more resistant to passivation. Compared with pure titanium anodes, Ti-based TiMn coated anodes not only retain the excellent comprehensive mechanical properties provided by the pure Ti matrix, but also have better wettability, lower cell voltage, and better anti-passivation ability.

[0005] At present, the main method for preparing Ti-based TiMn coated anodes is the high-temperature manganese infiltration process. Although this process alleviates the passive corrosion of the anode to a certain extent, it still has defects, such as the limited Mn content on the surface of the anode plate, which leads to limited performance of the final anode plate, and Mn is easy to volatilize and diffuse under vacuum and high temperature, the manganese infiltration efficiency is low, and the manganese source is seriously wasted. In addition, under high temperature environment, the αTi grains in the Ti matrix are coarse, and β-titanium transformation occurs. After cooling, a lamellar β-titanium transformation structure is obtained, which increases the brittleness of the Ti plate. The anode is easy to break during the production of mechanical stripping of manganese dioxide.

[0006] The rapid development of new energy has put forward requirements for improving the quality and energy saving of electrolytic MnO2, which is an important raw material for batteries. At present, the anode materials used in electrolytic MnO2 are difficult to be used under conditions of high acidity and high current, resulting in low electrolysis efficiency, a small range of crystal type control of MnO2, low purity, and narrow performance control of electrolytic MnO2. Therefore, it is urgent to develop new anode materials to improve the comprehensive performance of anode materials, efficiently produce high-quality electrolytic MnO2, and promote the development of the new energy industry. Summary of the invention

[0007] The purpose of the present invention is to provide a titanium alloy anode plate and a preparation method thereof, which is used for electrolytic manganese dioxide production and has anti-passivation performance at 100A / m 2 Under the current density and normal industrial electrolysis conditions, the cell voltage can be stabilized within 2.3-2.4 volts. The product adheres well to the anode without cracking or separation, overcoming the defects of existing industrial anodes and being an ideal anode for electrolytic manganese dioxide.

[0008] The technical solution of the present invention is achieved in this way: The invention provides a method for preparing a titanium alloy anode plate. The method comprises the following steps: mixing Ti powder and Mn powder, ball milling and plasma spheroidizing to obtain spherical TiMn alloy powder, flame spraying the powder on the surface of a titanium plate, gradient manganese infiltration, and after surface treatment, uniformly spraying copper nanowire-deposited graphene@spherical TiMn alloy powder, and drying the powder to obtain a titanium alloy anode plate.

[0009] As a further improvement of the present invention, the following steps are included: S1. Plasma spheroidization: Ti powder and Mn powder are mixed, ball-milled under inert gas protection, and the product is subjected to plasma spheroidization to obtain spherical TiMn alloy powder; S2. Graphene oxide coating: Spherical TiMn alloy powder was added to an aqueous dispersion of graphene oxide and dried to obtain graphene oxide @ spherical TiMn alloy powder; S3. Preparation of copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder: adding graphene oxide @ spherical TiMn alloy powder and polyvinyl pyrrolidone to ethylene glycol, adding copper nitrate and ferric chloride, stirring and mixing, heating for reaction, centrifuging, washing, and drying to obtain copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder; S4. Reduction: reducing the copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder with hydrazine hydrate vapor to obtain copper nanowire-deposited graphene @ spherical TiMn alloy powder; S5. Flame spraying: Spherical TiMn alloy powder is flame sprayed onto the surface of the titanium plate, and the sprayed part is rapidly cooled by liquid nitrogen; S6. Manganese infiltration: The flame-sprayed anode plate is placed in a gradient manganese infiltration furnace for gradient manganese infiltration, and the surface is treated with sandblasting and oxalic acid hydrogenation to obtain a primary titanium alloy anode plate; S7. Surface spraying: adding copper nanowire-deposited graphene@spherical TiMn alloy powder into an organic solvent, dispersing it evenly, and then spraying it evenly on the surface of the primary titanium alloy anode plate, drying it, and obtaining a titanium alloy anode plate.

[0010] As a further improvement of the present invention, the mass ratio of the Ti powder to the Mn powder in step S1 is 1:2-4, the particle size of the Ti powder and the Mn powder is 40-55 μm, the ball milling conditions are: ball milling at a speed of 150-300 r / min for 0.5-1 h, ball milling at a speed of 500 r / min for 15-30 h, then reversing, ball milling at a speed of 500 r / min for 15-30 h, and the plasma spheroidization treatment conditions are: powder feeding rate 10-20 g / s, and the particle size of the spherical TiMn alloy powder obtained is 5-15 μm, sphericity>99%, and spheroidization rate>98%. The oxygen content in the Ti powder can be further reduced by plasma spheroidization.

[0011] As a further improvement of the present invention, the concentration of the graphene oxide aqueous dispersion in step S2 is 0.5-1.5 mg / mL, the solid-liquid ratio of the spherical TiMn alloy powder and the graphene oxide aqueous dispersion is 1:10-20 g / mL, and the drying is normal pressure or reduced pressure drying.

[0012] As a further improvement of the present invention, in step S3, the mass ratio of graphene oxide @ spherical TiMn alloy powder, polyvinyl pyrrolidone, copper nitrate and ferric chloride is 10:4-6:6-8:0.1-0.15, and the temperature of the heating reaction is 120-140°C and the time is 4-6h.

[0013] As a further improvement of the present invention, the time for the hydrazine hydrate steam reduction in step S4 is 10-12 hours.

[0014] As a further improvement of the present invention, the flame spraying conditions in step S5 are: oxygen flow rate is 1600-1900 SCFH, argon flow rate is 6-10 L / min, fuel flow rate is 4-6 GPH, intermittent spraying is adopted, spraying distance is 300-500 mm, coating thickness is 100-300 μm, and the liquid nitrogen rapid cooling method is to spray liquid nitrogen on the spraying part for cooling, and the spraying amount is 3-5 mL / cm 2 The titanium plate surface is subjected to low temperature degreasing and dehydrogenation treatment under the following conditions: -4 -10 -2Under the vacuum pressure of 100-120℃, keep the temperature for 0.5-1h, then keep the temperature for 2-4h at 350-550℃, and then keep the temperature for 1-2h at 550-600℃. The spraying part is fast cooled to make the alloy powder cool quickly, which plays a role in grain refinement.

[0015] As a further improvement of the present invention, the conditions of the gradient manganese infiltration in step S6 are: filling with inert gas to a pressure of 1Pa-25kPa, a heating rate of 3-8°C / min, a low temperature of 650°C-750°C, a holding time of 1-3h, a medium temperature of 700-800°C, a holding time of 2-4h, and a high temperature of 800-900°C, a holding time of 1-3h. The uniformity of manganese infiltration is controlled by the gradient temperature, and the manganese in the titanium-manganese alloy layer on the surface of the anode plate sprayed by flame is not easy to volatilize and diffuse, which improves the uniformity of manganese infiltration and improves the conductivity and mechanical properties of the anode plate.

[0016] As a further improvement of the present invention, the organic solvent in step S7 is selected from at least one of ethyl acetate, acetone, butyl acetate, ethanol, and propanol, and the solid-liquid ratio of the copper nanowire deposited graphene @ spherical TiMn alloy powder and the organic solvent is 1:5-10 g / mL.

[0017] The present invention further protects a titanium alloy anode plate prepared by the above preparation method.

[0018] The present invention has the following beneficial effects: The traditional sintering furnace vacuum manganese infiltration process is to coat pure Mn powder on the Ti substrate, and then hoist the Ti substrate as a whole into the sintering furnace for manganese infiltration. Due to the influence of factors such as the size of the sintering furnace and the uniformity of the temperature field, it is difficult to prepare a large-sized Ti-based Ti-Mn coating anode with uniform infiltration layer thickness, microstructure, and manganese content. The flame spraying technology and multi-layer conductive layer structure proposed in the present invention for preparing titanium alloy anode plates have the following innovations compared to traditional preparation technologies: The flame spraying technology of the present invention can meet the requirements of the surface coating of Ti plates of any size, while the size of the anode plate produced by the traditional vacuum furnace manganese infiltration technology is limited by the size of the inner cavity of the sintering furnace. The flame spraying technology is used for the preparation of the first coating on the surface of the titanium alloy anode plate. By adjusting the spraying time, speed, temperature and powder feeding amount, the coating thickness can be accurately controlled. In the traditional vacuum furnace high-temperature manganese infiltration process, due to the influence of the furnace temperature uniformity, the manganese at different positions of the Ti plate volatilizes differently during the high-temperature manganese infiltration, which will lead to uneven thickness of the infiltration layer.

[0019] The plasma spheroidization technology used in the present invention can further increase the sphericity and spheroidization rate of the TiMn alloy powder and reduce the oxygen content in the Ti layer. The increase in the sphericity and spheroidization rate can ensure the fluidity and uniformity of the powder during flame spraying, and the low oxygen content can increase the bonding of the spray coating. By using flame spraying technology combined with high-energy ball milling to prepare pre-alloyed powder, the Ti-Mn coating alloy structure can be independently controlled by adjusting the spraying parameters. By adjusting the spraying parameters to ensure the consistency of spraying everywhere, the fluctuation of manganese content in the coating can be strictly controlled, which is beneficial to improving product quality.

[0020] The flame spraying technology and the method of substrate supercooling treatment can avoid the long-term heating of the Ti substrate as a whole, thereby reducing the tendency of grain coarsening of the Ti substrate, which is beneficial to improving the overall mechanical properties of the titanium alloy anode plate. At the same time, the substrate after rapid supercooling treatment with liquid nitrogen can refine the grains of the sprayed TiMn alloy and make the coating dense.

[0021] The TiMn alloy powder prepared by mechanical alloying in the present invention has a lower melting point than pure Mn powder, can be flame sprayed at a lower temperature, reduces the tendency of grain coarsening of the titanium matrix, and is beneficial to improving the overall mechanical properties of the titanium alloy anode plate.

[0022] When using traditional vacuum manganese infiltration, due to the easy evaporation of manganese, a large amount of manganese powder on the surface of the Ti substrate evaporates. This makes it difficult for the manganese content of the infiltration layer obtained by this technology to exceed 20wt%. The present invention uses mechanical alloying technology to prepare Ti-Mn alloy powder with high Mn content in advance and then sprays it, so that a coating with high surface manganese content can be obtained, which can break through the limitations of traditional technology.

[0023] The invention adopts a multilayer structure, wherein the first layer is a TiMn alloy powder which is flame-sprayed on a titanium plate and gradiently manganese-infiltrated to obtain a gradient layer with different manganese contents, which can significantly change the electronic structure and conductive properties of the Ti alloy, and the introduction of Mn can reduce the band gap of the oxide film on the surface of the Ti alloy, thereby gradually improving the conductivity of the anode plate, and the gradient structure can reduce the interface resistance, while providing higher conductivity in a high Mn content region, and maintaining good mechanical properties in a low Mn content region, thereby effectively improving the conductivity and service life of the anode plate; the second layer is a copper nanowire-deposited graphene@spherical TiMn alloy powder layer, wherein the copper nanowire is deposited on the surface, has a nanostructure, and has excellent conductivity, and due to the nanostructure, the surface structure of the anode plate is improved, and the nanostructure increases the specific surface area, exposing more active sites, thereby improving the conductivity and reaction rate. Copper nanowires are deposited on graphene. Each carbon atom in graphene provides a π electron, which can move freely in the graphene lattice to form a long-range conjugated network, giving graphene an extremely high theoretical electron mobility, thereby making it extremely conductive. Moreover, before the reduction of graphene oxide, the oxygen-containing groups combine with copper nanoparticles through chemical bonds to form a stable composite structure, which not only enhances the dispersibility of the copper nanowires, but also effectively prevents their oxidation, thereby avoiding the impact of oxidation on the conductivity of the surface.

[0024] The electrolytic manganese dioxide produced by the present invention has anti-passivation performance and can withstand 100A / m 2 Under the current density and normal industrial electrolysis conditions, the cell voltage can be stabilized within 2.3-2.4 volts. The product adheres well to the anode without cracking or separation, overcoming the defects of existing industrial anodes and being an ideal anode for electrolytic manganese dioxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0026] Figure 1 This is a SEM image of the primary titanium alloy anode plate prepared in Example 3; Figure 2 This is the SEM image of the primary titanium alloy anode plate prepared in Comparative Example 1. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The particle size of Ti powder and Mn powder is 40-55μm. Graphene oxide, particle size D 50 The titanium plate is a TA1 titanium plate with a Ti content of 99.5%, a Fe content of 0.25%, an oxygen content of 0.18%, a carbon content of 0.04%, and a nitrogen content of 0.03%.

[0029] Example 1 This embodiment provides a method for preparing a titanium alloy anode plate, comprising the following steps: S1. Plasma spheroidization treatment: 1g Ti powder and 2g Mn powder are mixed, and ZrO2 ceramic balls are selected as grinding balls according to a ball-to-material ratio of 11:1 (mass ratio). The grinding balls include 10mm grinding balls and 3mm grinding balls, and the proportion of 10mm grinding balls: 3mm grinding balls is 6:4. At the same time, the air is replaced, and nitrogen is filled in for protection to prevent the Ti powder from being oxidized. Ball milling is performed at a speed of 150r / min for 0.5h, and at a speed of 500r / min for 15h. Then, the ball milling is reversed and at a speed of 500r / min for 15h. The product is loaded into a plasma spheroidization powder feeding device at a powder feeding rate of 10g / s, and a spherical TiMn alloy powder having a particle size of 5-15μm, a sphericity of>99%, and a spheroidization rate of>98% is obtained. Spherical TiMn alloy powder is obtained; S2. Graphene oxide coating: 1 g of spherical TiMn alloy powder was added to 10 mL of 1.5 mg / mL graphene oxide aqueous dispersion and dried at normal pressure to obtain graphene oxide @ spherical TiMn alloy powder; S3. Preparation of copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder: 10 g of graphene oxide @ spherical TiMn alloy powder and 4 g of polyvinyl pyrrolidone were added to 500 mL of ethylene glycol, 6 g of copper nitrate and 0.1 g of ferric chloride were added, and the mixture was stirred for 15 min, heated to 120°C, stirred for 4 h, centrifuged, washed, and dried to obtain copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder; S4. Reduction: The copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder was reduced with hydrazine hydrate vapor for 10 h to obtain copper nanowire-deposited graphene @ spherical TiMn alloy powder; S5. Flame spraying: Spherical TiMn alloy powder was sprayed onto the surface of the titanium plate by a supersonic flame spraying device. The flame spraying conditions were as follows: oxygen flow rate was 1600 SCFH, argon flow rate was 6 L / min, fuel flow rate was 4 GPH, intermittent spraying was adopted, spraying distance was 300 mm, coating thickness was 150 μm, liquid nitrogen was sprayed on the spraying part for cooling, and the spraying volume was 3 mL / cm 2 ; S6. Manganese infiltration: The flame sprayed anode plate is placed in a gradient manganese infiltration furnace for gradient manganese infiltration, and inert gas is filled to a pressure of 10 kPa, the heating rate is 3 ° C / min, the low temperature is 650 ° C, the heat preservation time is 1 hour, the medium temperature is 700 ° C, the heat preservation time is 2 hours, the high temperature is 800 ° C, the heat preservation time is 1 hour, and then sandblasting and oxalic acid surface hydrogenation treatment are performed, and the hydrogenation treatment time is 30 minutes to obtain a primary titanium alloy anode plate; S7. Surface spraying: 10 g of copper nanowire-deposited graphene@spherical TiMn alloy powder was added to 50 mL of ethyl acetate, ultrasonically dispersed at 1000 W for 15 min, and evenly sprayed on the surface of the primary titanium alloy anode plate, and dried to obtain a titanium alloy anode plate.

[0030] Example 2 This embodiment provides a method for preparing a titanium alloy anode plate, comprising the following steps: S1. Plasma spheroidization treatment: 1g Ti powder and 4g Mn powder are mixed, and ZrO2 ceramic balls are selected as grinding balls according to a ball-to-material ratio of 20:1 (mass ratio). The grinding balls include 10mm grinding balls and 3mm grinding balls, and the proportion of 10mm grinding balls: 3mm grinding balls = 8:2. At the same time, the air is replaced, and nitrogen is filled in for protection to prevent the Ti powder from being oxidized. Ball milling is performed at a speed of 300r / min for 1h, and at a speed of 500r / min for 30h. Then, the ball milling is reversed and at a speed of 500r / min for 30h. The product is loaded into a plasma spheroidization powder feeding device at a powder feeding rate of 20g / s. The particle size of the spherical TiMn alloy powder is 5-15μm, the sphericity is>99%, and the spheroidization rate is>98%. Spherical TiMn alloy powder is obtained; S2. Graphene oxide coating: 1 g of spherical TiMn alloy powder was added to 20 mL of 0.5 mg / mL graphene oxide aqueous dispersion and dried under normal pressure or reduced pressure to obtain graphene oxide @ spherical TiMn alloy powder; S3. Preparation of copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder: 10 g of graphene oxide @ spherical TiMn alloy powder and 6 g of polyvinyl pyrrolidone were added to 500 mL of ethylene glycol, 8 g of copper nitrate and 0.15 g of ferric chloride were added, and the mixture was stirred for 15 min, heated to 140°C, stirred for 6 h, centrifuged, washed, and dried to obtain copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder; S4. Reduction: The copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder was reduced with hydrazine hydrate vapor for 12 h to obtain copper nanowire-deposited graphene @ spherical TiMn alloy powder; S5. Flame spraying: Spherical TiMn alloy powder was sprayed onto the surface of the titanium plate by a supersonic flame spraying device. The flame spraying conditions were as follows: oxygen flow rate was 1900 SCFH, argon flow rate was 10 L / min, fuel flow rate was 6 GPH, intermittent spraying was adopted, spraying distance was 500 mm, coating thickness was 150 μm, liquid nitrogen was sprayed on the spraying part for cooling, and the spraying volume was 5 mL / cm 2 ; S6. Manganese infiltration: The flame sprayed anode plate is placed in a gradient manganese infiltration furnace for gradient manganese infiltration, and inert gas is filled to a pressure of 25 kPa, the heating rate is 8 ° C / min, the low temperature is 750 ° C, the heat preservation time is 3 hours, the medium temperature is 800 ° C, the heat preservation time is 4 hours, the high temperature is 900 ° C, the heat preservation time is 3 hours, and then sandblasting and oxalic acid surface hydrogenation treatment are performed, and the hydrogenation treatment time is 50 minutes to obtain a primary titanium alloy anode plate; S7. Surface spraying: 10 g of copper nanowire-deposited graphene@spherical TiMn alloy powder was added to 100 mL of acetone, ultrasonically dispersed at 1000 W for 15 min, and evenly sprayed on the surface of the primary titanium alloy anode plate, and dried to obtain a titanium alloy anode plate.

[0031] Example 3 This embodiment provides a method for preparing a titanium alloy anode plate, comprising the following steps: S1. Plasma spheroidization treatment: 1g Ti powder and 3g Mn powder are mixed, and ZrO2 ceramic balls are selected as grinding balls according to a ball-to-material ratio of 16:1 (mass ratio). The grinding balls include 10mm grinding balls and 3mm grinding balls, and the proportion of 10mm grinding balls: 3mm grinding balls = 7:3. At the same time, the air is replaced, and nitrogen is filled in for protection to prevent the Ti powder from being oxidized. Ball milling is performed at a speed of 200r / min for 1h, and at a speed of 500r / min for 20h. Then, the ball milling is reversed and at a speed of 500r / min for 20h. The product is loaded into a plasma spheroidization powder feeding device at a powder feeding rate of 15g / s. The particle size of the spherical TiMn alloy powder is 5-15μm, the sphericity is>99%, and the spheroidization rate is>98%. Spherical TiMn alloy powder is obtained; S2. Graphene oxide coating: 1 g of spherical TiMn alloy powder was added to 15 mL of 1 mg / mL of graphene oxide aqueous dispersion, and dried under normal pressure or reduced pressure to obtain graphene oxide @ spherical TiMn alloy powder; S3. Preparation of copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder: 10 g of graphene oxide @ spherical TiMn alloy powder and 5 g of polyvinyl pyrrolidone were added to 500 mL of ethylene glycol, 7 g of copper nitrate and 0.12 g of ferric chloride were added, and the mixture was stirred for 15 min, heated to 130°C, stirred for 5 h, centrifuged, washed, and dried to obtain copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder; S4. Reduction: The copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder was reduced with hydrazine hydrate vapor for 11 h to obtain copper nanowire-deposited graphene @ spherical TiMn alloy powder; S5. Flame spraying: Spherical TiMn alloy powder was sprayed onto the surface of the titanium plate by a supersonic flame spraying device. The flame spraying conditions were as follows: oxygen flow rate was 1750 SCFH, argon flow rate was 8 L / min, fuel flow rate was 5 GPH, intermittent spraying was adopted, spraying distance was 400 mm, coating thickness was 150 μm, liquid nitrogen was sprayed on the spraying part for cooling, and the spraying volume was 4 mL / cm 2 ; S6. Manganese infiltration: The flame sprayed anode plate is placed in a gradient manganese infiltration furnace for gradient manganese infiltration, and inert gas is filled to a pressure of 15 kPa, the heating rate is 5 ° C / min, the low temperature is 700 ° C, the heat preservation time is 2 hours, the medium temperature is 750 ° C, the heat preservation time is 3 hours, the high temperature is 850 ° C, the heat preservation time is 2 hours, and then sandblasting and oxalic acid surface hydrogenation treatment are performed for 40 minutes to obtain a primary titanium alloy anode plate; the microscopic morphology of the obtained primary titanium alloy anode plate is analyzed, and its SEM image is as follows Figure 1 ,from Figure 1 It can be seen that the surface coating is dense and the coating thickness is about 150μm. After testing, the surface Mn content is 39%.

[0032] S7. Surface spraying: 10 g of copper nanowire-deposited graphene@spherical TiMn alloy powder was added to 70 mL of ethanol, ultrasonically dispersed at 1000 W for 15 min, and evenly sprayed on the surface of the primary titanium alloy anode plate, and dried to obtain a titanium alloy anode plate.

[0033] Comparative Example 1 Compared with Example 3, the difference is that no plasma spheroidization treatment is performed in step S1.

[0034] The details are as follows: (1) Ball milling: 1 g of Ti powder and 3 g of Mn powder were mixed, and ZrO2 ceramic balls were selected as grinding balls at a ball-to-material ratio of 16:1 (mass ratio). The grinding balls included 10 mm grinding balls and 3 mm grinding balls, and the ratio of 10 mm grinding balls to 3 mm grinding balls was 7:3. At the same time, the air was replaced and nitrogen was introduced to prevent oxidation of the Ti powder. The mixture was ball milled at a speed of 200 r / min for 1 h, and at a speed of 500 r / min for 20 h. The mixture was then reversed and ball milled at a speed of 500 r / min for 20 h to obtain TiMn alloy powder.

[0035] The primary titanium alloy anode plate obtained in step S6 was subjected to microscopic morphology analysis, and its SEM image is as follows: Figure 2 ,from Figure 2 It can be seen that the coating is not smooth and uniform, and has many defects. After testing, the Mn content on its surface is 16.2%.

[0036] Comparative Example 2 Compared with Example 3, the difference is that steps S2 and S4 are not performed.

[0037] The details are as follows: (1) Plasma spheroidization treatment: 1 g Ti powder and 3 g Mn powder were mixed, and ZrO2 ceramic balls were selected as grinding balls according to a ball-to-material ratio of 16:1 (mass ratio). The grinding balls included 10 mm grinding balls and 3 mm grinding balls, and the ratio of 10 mm grinding balls to 3 mm grinding balls was 7:3. At the same time, the air was replaced and nitrogen was filled in to protect the Ti powder from oxidation. The mixture was ball-milled at a speed of 200 r / min for 1 h, and at a speed of 500 r / min for 20 h. The mixture was then reversed and ball-milled at a speed of 500 r / min for 20 h. The product was loaded into a plasma spheroidization powder feeding device at a powder feeding rate of 15 g / s. The obtained spherical TiMn alloy powder had a particle size of 5-15 μm, a sphericity of >99%, and a spheroidization rate of >98%. Spherical TiMn alloy powder was obtained. (2) Preparation of copper nanowires @ spherical TiMn alloy powder: 10 g of spherical TiMn alloy powder and 5 g of polyvinyl pyrrolidone were added to 500 mL of ethylene glycol, and 7 g of copper nitrate and 0.12 g of ferric chloride were added. The mixture was stirred for 15 min, heated to 130 °C, stirred for 5 h, centrifuged, washed, and dried to obtain copper nanowires @ spherical TiMn alloy powder. (3) Flame spraying: Spherical TiMn alloy powder was sprayed onto the surface of the titanium plate by a supersonic flame spraying device. The flame spraying conditions were as follows: oxygen flow rate was 1750 SCFH, argon flow rate was 8 L / min, fuel flow rate was 5 GPH, intermittent spraying was adopted, the spraying distance was 400 mm, the coating thickness was 150 μm, and liquid nitrogen was sprayed on the spraying part for cooling. The spraying volume was 4 mL / cm 2 ; (4) Manganese infiltration: The flame sprayed anode plate is placed in a gradient manganese infiltration furnace for gradient manganese infiltration, and inert gas is filled to a pressure of 15 kPa, the heating rate is 5 ° C / min, the low temperature is 700 ° C, the insulation time is 2 h, the medium temperature is 750 ° C, the insulation time is 3 h, the high temperature is 850 ° C, the insulation time is 2 h, and then sandblasting and oxalic acid surface hydrogenation treatment are performed. The hydrogenation treatment time is 40 minutes to obtain a primary titanium alloy anode plate.

[0038] (5) Surface spraying: 10 g of copper nanowires@spherical TiMn alloy powder was added to 70 mL of ethanol, ultrasonically dispersed at 1000 W for 15 min, and evenly sprayed on the surface of the primary titanium alloy anode plate. After drying, a titanium alloy anode plate was obtained.

[0039] Comparative Example 3 Compared with Example 3, the difference is that step S3 is not performed.

[0040] The details are as follows: (1) Plasma spheroidization treatment: 1 g Ti powder and 3 g Mn powder were mixed, and ZrO2 ceramic balls were selected as grinding balls according to a ball-to-material ratio of 16:1 (mass ratio). The grinding balls included 10 mm grinding balls and 3 mm grinding balls, and the ratio of 10 mm grinding balls to 3 mm grinding balls was 7:3. At the same time, the air was replaced and nitrogen was filled in to protect the Ti powder from oxidation. The mixture was ball-milled at a speed of 200 r / min for 1 h, and at a speed of 500 r / min for 20 h. The mixture was then reversed and ball-milled at a speed of 500 r / min for 20 h. The product was loaded into a plasma spheroidization powder feeding device at a powder feeding rate of 15 g / s. The obtained spherical TiMn alloy powder had a particle size of 5-15 μm, a sphericity of >99%, and a spheroidization rate of >98%. Spherical TiMn alloy powder was obtained. (2) Graphene oxide coating: 1 g of spherical TiMn alloy powder was added into 15 mL of 1 mg / mL graphene oxide aqueous dispersion and dried under normal pressure or reduced pressure to obtain graphene oxide@spherical TiMn alloy powder; (3) Reduction: The graphene oxide @ spherical TiMn alloy powder is reduced with hydrazine hydrate vapor for 11 hours to obtain graphene @ spherical TiMn alloy powder; (4) Flame spraying: Spherical TiMn alloy powder was sprayed onto the surface of the titanium plate by a supersonic flame spraying device. The flame spraying conditions were as follows: oxygen flow rate was 1750 SCFH, argon flow rate was 8 L / min, fuel flow rate was 5 GPH, intermittent spraying was adopted, the spraying distance was 400 mm, the coating thickness was 150 μm, and liquid nitrogen was sprayed on the spraying part for cooling, and the spraying volume was 4 mL / cm 2 ; (5) Manganese infiltration: The flame sprayed anode plate is placed in a gradient manganese infiltration furnace for gradient manganese infiltration, and inert gas is filled to a pressure of 15 kPa, the heating rate is 5 ° C / min, the low temperature is 700 ° C, the insulation time is 2 h, the medium temperature is 750 ° C, the insulation time is 3 h, the high temperature is 850 ° C, the insulation time is 2 h, and then sandblasting and oxalic acid surface hydrogenation treatment, the hydrogenation treatment time is 40 min, and the primary titanium alloy anode plate is obtained.

[0041] (6) Surface spraying: 10 g of graphene@spherical TiMn alloy powder was added to 70 mL of ethanol, ultrasonically dispersed at 1000 W for 15 min, and evenly sprayed on the surface of the primary titanium alloy anode plate. After drying, a titanium alloy anode plate was obtained.

[0042] Comparative Example 4 Compared with the embodiment 3, the difference is that steps S5 and S6 are not performed.

[0043] The details are as follows: (1) Plasma spheroidization treatment: 1 g Ti powder and 3 g Mn powder were mixed, and ZrO2 ceramic balls were selected as grinding balls according to a ball-to-material ratio of 16:1 (mass ratio). The grinding balls included 10 mm grinding balls and 3 mm grinding balls, and the ratio of 10 mm grinding balls to 3 mm grinding balls was 7:3. At the same time, the air was replaced and nitrogen was filled in to protect the Ti powder from oxidation. The mixture was ball-milled at a speed of 200 r / min for 1 h, and at a speed of 500 r / min for 20 h. The mixture was then reversed and ball-milled at a speed of 500 r / min for 20 h. The product was loaded into a plasma spheroidization powder feeding device at a powder feeding rate of 15 g / s. The obtained spherical TiMn alloy powder had a particle size of 5-15 μm, a sphericity of >99%, and a spheroidization rate of >98%. Spherical TiMn alloy powder was obtained. (2) Graphene oxide coating: 1 g of spherical TiMn alloy powder was added into 15 mL of 1 mg / mL graphene oxide aqueous dispersion and dried under normal pressure or reduced pressure to obtain graphene oxide@spherical TiMn alloy powder; (3) Preparation of copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder: 10 g of graphene oxide @ spherical TiMn alloy powder and 5 g of polyvinyl pyrrolidone were added to 500 mL of ethylene glycol, 7 g of copper nitrate and 0.12 g of ferric chloride were added, and the mixture was stirred for 15 min, heated to 130 ° C, stirred for 5 h, centrifuged, washed, and dried to obtain copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder; (4) Reduction: subjecting the copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder to hydrazine hydrate vapor reduction for 11 h to obtain copper nanowire-deposited graphene @ spherical TiMn alloy powder; (5) Surface spraying: The titanium plate was pre-treated by sandblasting and oxalic acid surface hydrogenation for 40 min to obtain a pre-treated titanium plate. 10 g of copper nanowire-deposited graphene@spherical TiMn alloy powder was added to 70 mL of ethanol and ultrasonically dispersed at 1000 W for 15 min. The powder was evenly sprayed on the surface of the pre-treated titanium plate and dried to obtain a titanium alloy anode plate.

[0044] Comparative Example 5 Compared with the embodiment 3, the difference is that step S7 is not performed.

[0045] The details are as follows: (1) Plasma spheroidization treatment: 1 g Ti powder and 3 g Mn powder were mixed, and ZrO2 ceramic balls were selected as grinding balls according to a ball-to-material ratio of 16:1 (mass ratio). The grinding balls included 10 mm grinding balls and 3 mm grinding balls, and the ratio of 10 mm grinding balls to 3 mm grinding balls was 7:3. At the same time, the air was replaced and nitrogen was filled in to protect the Ti powder from oxidation. The mixture was ball-milled at a speed of 200 r / min for 1 h, and at a speed of 500 r / min for 20 h. The mixture was then reversed and ball-milled at a speed of 500 r / min for 20 h. The product was loaded into a plasma spheroidization powder feeding device at a powder feeding rate of 15 g / s. The obtained spherical TiMn alloy powder had a particle size of 5-15 μm, a sphericity of >99%, and a spheroidization rate of >98%. Spherical TiMn alloy powder was obtained. (2) Flame spraying: Spherical TiMn alloy powder was sprayed onto the surface of the titanium plate by a supersonic flame spraying device. The flame spraying conditions were as follows: oxygen flow rate was 1750 SCFH, argon flow rate was 8 L / min, fuel flow rate was 5 GPH, intermittent spraying was adopted, the spraying distance was 400 mm, the coating thickness was 150 μm, and liquid nitrogen was sprayed on the spraying part for cooling. The spraying volume was 4 mL / cm 2 ; (3) Manganese infiltration: The flame sprayed anode plate is placed in a gradient manganese infiltration furnace for gradient manganese infiltration, and inert gas is filled to a pressure of 15 kPa, the heating rate is 5 ° C / min, the low temperature is 700 ° C, the insulation time is 2 h, the medium temperature is 750 ° C, the insulation time is 3 h, the high temperature is 850 ° C, the insulation time is 2 h, and then sandblasting and oxalic acid surface hydrogenation treatment are performed. The hydrogenation treatment time is 40 min to obtain a titanium alloy anode plate.

[0046] Test Example 1 The titanium alloy anode plates prepared in Examples 1-3 and Comparative Examples 1-5 were tested for mechanical properties. The results are shown in Table 1.

[0047] Table 1

[0048] It can be seen from the above table that the titanium alloy anode plates prepared in Examples 1-3 of the present invention have good mechanical properties.

[0049] Test Example 2 The titanium alloy anode plates prepared in Examples 1-3 and Comparative Examples 1-5 were subjected to normal industrial electrolysis conditions at 100 A / m 2 When the current density is , the performance is tested and the results are shown in Table 2.

[0050] Table 2

[0051] As can be seen from the table above, the titanium alloy anode plates prepared in Examples 1-3 of the present invention have a high conductivity at 100 A / m 2 When the current density is high, the cell voltage is stable within 2.3-2.4V, and the MnO2 electrolysis efficiency is high.

[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a titanium alloy anode plate, characterized in that: The following steps are involved: S1. Plasma spheroidization: Ti powder and Mn powder are mixed, ball-milled under inert gas protection, and the product is subjected to plasma spheroidization to obtain spherical TiMn alloy powder; S2. Graphene oxide coating: Spherical TiMn alloy powder was added to an aqueous dispersion of graphene oxide and dried to obtain graphene oxide @ spherical TiMn alloy powder; S3. Preparation of copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder: adding graphene oxide @ spherical TiMn alloy powder and polyvinyl pyrrolidone to ethylene glycol, adding copper nitrate and ferric chloride, stirring and mixing, heating for reaction, centrifuging, washing, and drying to obtain copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder; S4. Reduction: reducing the copper nanowire-deposited graphene oxide @ spherical TiMn alloy powder with hydrazine hydrate vapor to obtain copper nanowire-deposited graphene @ spherical TiMn alloy powder; S5. Flame spraying: Spherical TiMn alloy powder is flame sprayed onto the surface of the titanium plate, and the sprayed part is rapidly cooled by liquid nitrogen; S6. Manganese infiltration: The flame-sprayed anode plate is placed in a gradient manganese infiltration furnace for gradient manganese infiltration, and the surface is treated with sandblasting and oxalic acid hydrogenation to obtain a primary titanium alloy anode plate; S7. Surface spraying: adding copper nanowire-deposited graphene@spherical TiMn alloy powder into an organic solvent, dispersing it evenly, and then spraying it evenly on the surface of the primary titanium alloy anode plate, drying it, and obtaining a titanium alloy anode plate.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the Ti powder to the Mn powder in step S1 is 1:2-4, the particle size of the Ti powder and the Mn powder is 40-55 μm, the ball milling conditions are: ball milling at a speed of 150-300 r / min for 0.5-1 h, ball milling at a speed of 500 r / min for 15-30 h, then reversing, and ball milling at a speed of 500 r / min for 15-30 h, the conditions of the plasma spheroidization treatment are: powder feeding rate 10-20 g / s, and the particle size of the spherical TiMn alloy powder obtained is 5-15 μm, the sphericity is>99%, and the spheroidization rate is>98%.

3. The preparation method according to claim 1, characterized in that: The concentration of the graphene oxide aqueous dispersion in step S2 is 0.5-1.5 mg / mL, the solid-liquid ratio of the spherical TiMn alloy powder and the graphene oxide aqueous dispersion is 1:10-20 g / mL, and the drying is drying under normal pressure or reduced pressure.

4. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of graphene oxide @ spherical TiMn alloy powder, polyvinyl pyrrolidone, copper nitrate and ferric chloride is 10:4-6:6-8:0.1-0.15, the temperature of the heating reaction is 120-140° C., and the time is 4-6 hours.

5. The preparation method according to claim 1, characterized in that: The time for the hydrazine hydrate steam reduction in step S4 is 10-12 hours.

6. The preparation method according to claim 1, characterized in that: The flame spraying conditions in step S5 are: oxygen flow rate is 1600-1900 SCFH, argon flow rate is 6-10 L / min, fuel flow rate is 4-6 GPH, intermittent spraying is adopted, spraying distance is 300-500 mm, coating thickness is 100-300 μm, and the liquid nitrogen rapid cooling method is to spray liquid nitrogen on the spraying part for cooling, and the spraying amount is 3-5 mL / cm 2 The titanium plate surface is subjected to low temperature degreasing and dehydrogenation treatment under the following conditions: -4 -10 -2 Under the vacuum pressure of Pa, first keep it at 100-120℃ for 0.5-1h, then keep it at 350-550℃ for 2-4h, and then keep it at 550-600℃ for 1-2h.

7. The preparation method according to claim 1, characterized in that: The conditions for the gradient manganese infiltration in step S6 are: filling with inert gas to a pressure of 1Pa-25kPa, a heating rate of 3-8°C / min, a low temperature of 650°C-750°C, a holding time of 1-3h, a medium temperature of 700-800°C, a holding time of 2-4h, and a high temperature of 800-900°C, a holding time of 1-3h.

8. The preparation method according to claim 1, characterized in that: The organic solvent in step S7 is selected from at least one of ethyl acetate, acetone, butyl acetate, ethanol, and propanol, and the solid-liquid ratio of the copper nanowire deposited graphene @ spherical TiMn alloy powder and the organic solvent is 1:5-10 g / mL.

9. A titanium alloy anode plate obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of Ti-Mn-diffusion titanium anode plate for electrolytic manganese dioxide

    CN101694001A

  • Preparation method of conductive reduced graphene oxide coated copper nanowire composite

    CN108707997A

  • Hybrid conductive material based on silver nanowires growing on graphene in situ and preparation method and application of hybrid conductive material

    CN109336091A

  • Nuclear radiation-resistant structural material and preparation method thereof

    CN113061832A

  • Improved anode material and anode for rechargeable battery, method of production thereof and electrochemical cell made therefrom

    CN113454805A